The relationship between organizational climate and job burnout The mediating role of administrative empowerment: An analytical study of the opinions of employees in the Babil Governorate Traffic Directorate / Traffic Complex for Vehicle Registration and - Obaid, Ahmed Hadi; Bahr, Maysam Riad; Noman, Areej Taher (Al-Ghary Journal of Economic and Administrative Sciences, 2022)
The aim of the current research is to know the level of direct impact of the relationship between the organizational climate represented by (organizational justice, organizational support, participation in organizational decisions) and job burnout represented by (emotional exhaustion, depersonalization, low personal achievement), and then measure the extent of that intensification. Impact or not through the interaction of administrative empowerment represented by (Meaning, Competence, Autonomy, Impact) as a mediating variable in the relationship between the two variables. For the purpose of reaching the results related to the research variables through the questionnaire prepared as a main tool for collecting the primary data related to the research, (55) questionnaires were distributed to the employees working in the traffic complex for vehicle registration and driving licenses in Babil Governorate. The number of retrieved and valid questionnaires for statistical analysis was (43) forms, and the statistical analysis program SPSS v.24 was used to analyze data and extract results related to describing and diagnosing research variables, testing its hypotheses, and verifying data accuracy, content validity and consistency using some statistical measures. The research found a set of results, the most important of which is the presence of direct influence relationships with high moral significance between the organizational climate as an independent variable on the job burnout and its dimensions as a dependent variable, And this effect becomes stronger to explain the variation in job burnout when administrative empowerment is entered as a mediating variable in the indirect influence model, which reinforces the inverse significant relationship between organizational climate and job burnout.